Clinical and radiological outcomes of Extreme Lateral Interbody Fusion (XLIF) in the treatment of lumbar spondylodiscitis: A multi-center study - Tan, Yixiang; Mohamed Ramlee, Fadzrul Abbas; Harun, Mohd Hezery; Jaapar, Mohd Shahril; Tan, Chor Ngee (Cureus, 2024)
Introduction Lumbar pyogenic spondylodiscitis is a challenging and rare spinal infection with high morbidity, particularly in patients with comorbidities. While the extreme lateral interbody fusion (XLIF) technique is established in treating degenerative spinal conditions, its efficacy in managing spondylodiscitis is less well-studied. This study aims to evaluate the clinical and radiographic outcomes of the XLIF approach combined with posterior instrumentation in patients with lumbar spondylodiscitis. Method In a multi-center, retrospective cohort study, 15 patients (mean age 66; 62.5% male) diagnosed with pyogenic spondylodiscitis underwent XLIF with posterior percutaneous fixation between January 2018 and December 2022 at two Malaysian hospitals. Patients were selected based on strict inclusion criteria, including a confirmed single-level disc infection and a minimum follow-up of one year. Clinical outcomes, including Visual Analog Scale (VAS) pain scores, infection markers (C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), white blood cell (WBC)), and fusion rates, were recorded preoperatively and at six weeks, three months, six months, and one year postoperatively. Data were analyzed using appropriate statistical tests, with a significance level set at p<0.05. Results The study demonstrated a significant reduction in VAS scores, from a mean of 7 preoperatively to 1.87 at six weeks postoperatively, representing a 73.3% pain reduction (p<0.005). Mean blood loss was minimal (193.3 mL), and no patients required transfusions. Marked reductions in inflammatory markers were observed, with CRP, ESR, and WBC levels decreasing by 75%, 71.5%, and 38.5%, respectively, within the first six weeks (p<0.005). Radiological assessment showed a 100% fusion rate with a mean fusion time of 4.1 months. Complications were low, with only one case of screw malposition and one surgical site infection, both managed without further morbidity. Conclusion The XLIF approach with posterior instrumentation is a safe and effective intervention for lumbar spondylodiscitis, providing substantial pain relief, infection control, and reliable spinal fusion. These findings suggest XLIF as a viable surgical option for lumbar spondylodiscitis, especially for patients with multiple comorbidities, warranting consideration as a primary surgical strategy for this challenging condition